Cutting performance of thick steel plates up to 150 mm in thickness and large size pipes with a 10-kW fiber laser for dismantling of nuclear facilities. (December 2018) - Shin, Jae Sung; Oh, Seong Yong; Park, Hyunmin; Chung, Chin-Man; Seon, Sangwoo; Kim, Taek-Soo; Lee, Lim; Lee, Jonghwan
Highlights: Cutting of thick steel plates and large pipes with a 10 kW fiber laser was studied. Stainless steel and carbon steel plates of up to 100 mm were cut at a high speed. A 150-mm thick stainless steel plate was also able to be cut. A 165 mm diameter pipe was possible to be cut. Our system showed efficient cutting performance in terms of speed and thickness. Abstract: The cutting performance of thick steel plates and large size pipes with a 10 kW fiber laser was studied for the dismantling of nuclear facilities. First, thick steel plates of up to 100 mm were tried to be cut at a high speed. For the thickness of 100 mm, both stainless steel and carbon steel plates were cut at maximum cutting speeds of ∼30 mm/min. And narrow kerf widths of less than 5 mm were obtained for all cutting tests. Second, a 150-mm thick stainless steel plate near the cutting thickness limit was attempted to be cut. The specimen was able to be cut even with a low cutting speed of 3 mm/min. To the best of our knowledge, this thickness is the largest among the published reports with a laser power of 10 kW. And this corresponds to a cutting capability in which most thick structures in a nuclear reactor can be cut. In addition, large size stainless steel pipes were also attempted to be cut. For a 165 mm diameter pipe, it was possible to be cut at high speed by one scan at a speed of 50 mm/min and round trip scan at a speed of 100 mm/min. This result implies that high-speed cutting was also possible for most pipe-type components inside the nuclear reactor. As a result, our 10-kW laser cutting system showed very efficient cutting performance in terms of the cutting speed and thickness. Moreover, the cuttings showed narrow kerf widths of less than 5 mm even for very thick steel of up to 150 mm in thickness. In the future, it is expected that the results of this work will contribute to cutting thick metal structures as basic research data in the dismantling of nuclear facilities using a laser. In addition, it is also expected that this work will contribute to other industrial fields requiring a thick steel cutting technique.